Wastewater Treatment and Recycling with Microalgae in Cold Climate - Grönlund, Erik; Fröling, Morgan (Mittuniversitetet, Avdelningen för ekoteknik och hållbart byggande, 2014)
Resilient societies need technology with high recycling possibilities, as well as possibilities to treat wastewater with local ecosystem services as dominating driving forces.Modern wastewater treatment often suffers from the problem of being a linear system, rather than a recycling system. From a recycling point of view the nutrients in the wastewater is of highest interest.The use of microalgae has been proposed as collection systems for the nutrients, with several potential advantages: 1) they treat the wastewater further from a pathogenic point of view, 2) they produce a sludge of interesting biochemical quality depending on the species present in the treatment ponds, 3) they use the naturally occurring ecosystem services available at the wastewater treatment site in the form of sunlight, wind, and regional biodiversity of phytoplankton.The academic focus regarding microalgae use for wastewater treatment has to a large extent been on the “sunbelt”, between latitudes 35 North and South, respectively. However, a few investigations have been performed on northern and southern latitudes. This paper summarizes experiences from using microalgae for waste water treatment at northern latitudes in Sweden and present suggestions for further research.